Changes and Continuities of Hunting Practices from the Late Pleistocene to the Late Holocene Among Nomadic Societies of the Patagonian Plateaus - Miotti, Laura Lucía (2021)
The research developed from different lines of evidence in the central plateau of Santa Cruz and the Somuncura plateau of Rio Negro, provides information for approaching the hunting strategies carried out by hunter-gatherer societies who inhabited these massifs in the past. The information about both regions results from the analysis of archaeofauna, lithic technology, rock art, stone structures, special topographies and archaeological landscapes. In this work we introduce a summary of the progress achieved so far, from which we have managed to define patterns related to the hunting strategies developed in these Patagonian plateaus, and their variations along time. The results we discuss show changes in hunting strategies, linked to the incorporation of new technologies. While a close encounter strategy is proposed for the Pleistocene-Holocene transition and early Holocene, distance hunting strategies seem to become more relevant towards the mid and late Holocene. This change suggests that the tactics deployed over time tended to incorporate more social actors cooperating in hunting events.